Influence of Halal Label, Expiration Date, and Product Composition on Consumer Purchase Decisions Mediated by Purchase Intention at MSME Gallery - Amhar, Rovan; Achmad, Gusti Noorlitaria; Kuleh, Yohanes (PT. Riset Press International, 2025)
This study aims to analyze the influence of halal labels, expiration dates, and product composition on consumer purchase decisions with purchase intention as a mediating variable at the Etham Nusantara MSME Gallery in Samarinda. The research employed a quantitative approach using a survey method with questionnaires, analyzed through Structural Equation Modeling (SEM) with the assistance of SmartPLS. The results indicate that halal labels, expiration dates, and product composition have a positive and significant effect on both purchase intention and purchase decisions, while purchase intention is proven to mediate the influence of these three variables on consumer purchase decisions. These findings highlight the importance of product information transparency in enhancing consumer trust, purchase intention, and purchase decisions, as well as providing strategic implications for MSME actors and gallery managers in strengthening the competitiveness of local products in an increasingly competitive market.